Evaluation of the macromolecular structure of Huadian oil shale kerogen using molecular modeling. (1st October 2016) - Tong, Jianhui; Jiang, Xiumin; Han, Xiangxin; Wang, Xiaoye
Highlights: Six constitutional isomers of Huadian oil shale kerogen molecular model were constructed. One model was found to have good agreement between the calculated and experimental spectra. Geometry optimization and molecular dynamics calculation were performed on 3D structural models. Several 3D structures were generated, including the energy-minimum 3D structure. Van der Waals interactions have a greatest effect on the physical density of this kerogen. Abstract: Based on chemical structure analysis, supplemented with fast pyrolysis results, six constitutional isomers of two-dimensional (2D) molecular models of the Huadian oil shale (HDOS) kerogen were constructed. One model yielded good agreement between simulated and experimental 13 C NMR spectra. Geometry optimization and molecular dynamics calculation were performed on three-dimensional (3D) structural models translated from the optimized 2D model. Several 3D structures were generated, including an energy-minimum 3D structure. The simulated results show that van der Waals (vdW) interactions have a greatest effect on the physical density of the HDOS kerogen. In addition, the nonbonding interactions, especially vdW interactions arisen from various flexible chains, play important role in the stabilization of the energy-minimum 3D structure.